AN ACOUSTIC PHONETICS ANALYSIS OF ACEHNESE DIPHTHONGS - Fajar Fitrian; I Dewa Putu Wijana (IKIP Siliwangi, 2024)
This acoustic study aims to describe how the Acehnese oral diphthongs are produced by five males and five females Acehnese speakers from Sigli with Pidie dialect. They are new coming students at the universities in Banda Aceh. They were selected to produce six diphthongs ending with /i/. The data were recorded from speakers’ elicitating the target words containing rising diphthongs adopted from Yusuf (2013). The target word was repeated six times for six diphthongs.; then gaining 360 tokens in total. The ROC is suggested by Gay (1968) to obtain the diphthongs movement. To obtain ROC, F1 and F2 were calculated as the mean values in Hertz using PRAAT version 6.4.07. 10% onset and offset were applied to decide both F1 and F2; their values are used in a formula reproduced from Yusuf (2013) to find out the ROC of each diphthong. The /əi/ for both gender indicated a short movement; Female /oi/ has a small average F1 ROC value, which indicates that the vowel height has not changed.. The /ʌi/ production seems close to /oi/ and the shift of offset /ɔi/ is preceived to be centered within the vowel space.